Special disability pension and periodic humanitarian provision for victims of the armed conflict in Colombia - Huertas Mendivelso, Diana Yeimy; Pérez González, Luis Milciades (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The investigation inquire into the promulgation of public policies, norms and actions carried out to guarantee the rights of the victims of the internal armed conflict affected in their personal integrity, in particular what at the time (1997) was called Special Disability Pension for Victims of Violence (PEI) and that as of 2017 was modified to Periodic Humanitarian Benefit for Victims of Armed Conflict (PHP), in the span of the last twenty years (1997-2017). The research focuses specifically on this type of victims and what has happened so far with them in terms of repair through the PEI or PHP. The findings obtained allow us to measure the magnitude of the problem faced by this population in its particular condition as victims of the armed conflict. It also serves as evidence that the entities responsible for guaranteeing the rights of this population have support that optimizes their management. The results of this investigation are useful for victims to have greater clarity of their situation and how they can demand the fulfillment of their rights. Also, they demonstrate the serious omission or failures of the State in these types of cases. A third impact of the results of this investigation is the possible contribution in information and evidence to the challenge of the implementation of peace agreements between the national government and the FARC, in terms of reparation for their victims.